Influência do hipoestrogenismo por ooforectomia na adaptação antioxidante em ratas wistar exercitadas regularmente - Marcedo, Ulisvaldo Brunno de Oliveira (2009)
Post-menopause is a period of women s life cycle that is characterized by estrogen depletion and therefore increasing cardiovascular diseases, neurodegenerative disorders, urogenital atrophy, osteoporosis, hot flushes and sexual discomfort incidences. Estrogen is a hormone with comfirmed antioxidant action and its depletion is related to oxidative stress instalation and damaging various important biomolecules. Regular physical activity has been identified as a factor involved in reducing women s post-menopausal complications in addition to improving antioxidant defense by reducing the oxidative damage and consequently improving life s quality in this part of the population. This study aims to evaluate the influence of hypoestrogenism in antioxidant adaptation due to regular exercise, by determining reduced glutathione (GSH) and Thiobarbituric Acid Reactive Substances (SRAT) concentrations and antioxidant enzymes glutathione peroxidase (GPx), Superoxide Dismutase (SOD) and Catalase (CAT) activities in blood, brain and liver of rats. To achieve this goal we used 50 Wistar rats, weighing 180-250g which were divided into two groups, control - GC (25) and ooforectomized - GO (25). Each group was subdivided into five subgroups: Not-trained - S (5), Not-trained Acute Exercise - SEA (5), regular exercise 30 days - E30 (5), regular exercise 60 days - E60 (5) and regular exercise 90 days - E90 (5). Each of the three subgroups exercised regularly was subjected to acute exercise on the eve and the day of sacrifice to collect biological samples of blood, liver and brain and subsequent determination of SRAT concentration, GSH content and antioxidant enzymes GPx, SOD and CAT activities. The results indicated that the sedentary animals acutely exercised presented oxidative stress and regular physical activity led to antioxidant adaptation. In ooforectomized group the antioxidant adaptation seen in control animals showed to be impaired. Unlike the results from blood and liver, in brain there was a shield against oxidative damage originated by the exercise and that hypoestrogenism led to a loss of this natural antioxidant potential. Therefore, hypoestrogenism interferes negatively in antioxidant adaptation due to regular exercise